Simultaneous improvement of thermal conductivities and electromagnetic interference shielding performances in polystyrene composites via constructing interconnection oriented networks based on electrospinning technology. (September 2019) - Guo, Yongqiang; Pan, Lulu; Yang, Xutong; Ruan, Kunpeng; Han, Yixin; Kong, Jie; Gu, Junwei
Abstract: Polymer composites with dual functions of thermal conductivity and electromagnetic interference (EMI) shielding are hardly reported. Herein, we fabricated polystyrene (PS) based composites containing interconnection oriented graphite nanoplatelets (GNPs) by the combining method of electrospinning, cold-pressing followed by hot-pressing. In-plane thermal conductivity ( λ = ) and total SE (SET ) of the oriented GNPs/PS composites with 35 wt% GNPs reached 4.72 W/mK and 33 dB, about 24 and 11 times higher than that of λ = (0.20 W/mK) and SET (3 dB) of pure PS matrix, and also higher than that of λ = (3.05 W/mK) and SET (16 dB) of the random 35 wt% GNPs/PS composites. However, the cross-plane λ ( λ ⊥ ) value for oriented GNPs/PS composites was slightly enhanced from 0.20 W/mK to 0.32 W/mK. This work provides a simple and effective method to construct continuously thermally/electrically conductive networks, and the obtained GNPs/PS composites have great application potential in the electronic fields.